Loading and composite restoration assessment of various non‐carious cervical lesions morphologies – 3D finite element analysis. (September 2015) - Soares, PV; Machado, AC; Zeola, LF; Souza, PG; Galvão, AM; Montes, TC; Pereira, AG; Reis, BR; Coleman, TA; Grippo, JO
Abstract Background The present study analysed the effects of different occlusal loading on premolars displaying various non‐carious cervical lesions morphologies, restored (or not) with composites, by 3D finite element analysis. Methods A three‐dimensional digital model of a maxillary premolar was generated using CAD software. Three non‐carious cervical lesions morphological types were simulated: wedged‐shaped, saucer and mixed. All virtual models underwent three loading types (100 N): vertical, buccal and palatal loading. The simulated non‐carious cervical lesions morphologies were analysed with and without restorations to consider specific regions, such as the occlusal and gingival walls as well as the depth of the lesions. Data summarizing the stress distribution were obtained in MPa using Maximum Principal Stress. Results Palatal loads were responsible for providing the highest values of accumulated tensile stress on the buccal wall; 27.66 MPa and 25.76 MPa for mixed and wedged‐shaped morphologies, respectively. The highest tensile values found on non‐carious cervical lesions morphologies restored with composite resin were 5.9 MPa in the mixed morphology, similar to those found on sound models despite their morphologies and occlusal loading. Conclusions The various non‐carious cervical lesions morphologies had little effect on stress distribution patterns, whereas the loading type and presence of composite restorations influenced the biomechanical behaviour of the maxillary premolars.